Transcriptome Analysis Reveals Olfactory System Expression Characteristics of Aquatic Snakes - Peng, Zhong-Liang; Wu, Wei; Tang, Chen-Yang; Ren, Jin-Long; Jiang, Dechun; Li, Jia-Tang (Frontiers in Genetics, 2022)
Animal olfactory systems evolved with changes in habitat to detect odor cues from the environment. The aquatic environment, as a unique habitat, poses a formidable challenge for olfactory perception in animals, since the higher density and viscosity of water. The olfactory system in snakes is highly specialized, thus providing the opportunity to explore the adaptive evolution of such systems to unique habitats. To date, however, few studies have explored the changes in gene expression features in the olfactory systems of aquatic snakes. In this study, we carried out RNA sequencing of 26 olfactory tissue samples (vomeronasal organ and olfactory bulb) from four aquatic and non-aquatic snakes to explore gene expression changes under the aquatic environment. Weighted gene co-expression network analysis showed significant differences in gene expression profiles between aquatic and non-aquatic habitats. The main olfactory systems of the aquatic and non-aquatic snakes were regulated by different genes. Among these genes, RELN may contribute to exploring gene expression changes under the aquatic environment by regulating the formation of inhibitory neurons in the granular cell layer and increasing the separation of neuronal patterns to correctly identify complex chemical information. The high expression of TRPC2 and V2R family genes in the accessory olfactory systems of aquatic snakes should enhance their ability to bind water-soluble odor molecules, and thus obtain more information in hydrophytic habitats. This work provides an important foundation for exploring the olfactory adaptation of snakes in special habitats.